The Influence of Leadership and Achievement Motivation on the Performance of Social Sciences Teachers at Private Junior High School Pekanbaru - Nina Febriana; Syakdanur Syakdanur; Henny Indrawati (Journal of Educational Sciences, 2020)
This study aims to identify and analyze the influence of leadership and achievement motivation on the performance of social studies (IPS) teachers at Pekanbaru Private Junior High School. The total population was 129 teachers. A sample of 32 people was obtained using a proportional random sampling technique. Data were collected by means of a questionnaire, then analyzed by descriptive analysis and path analysis. The results of the study found: (1) the leadership of the principal has an effect on the achievement motivation of social studies teachers at Pekanbaru Private Junior High School. The meaning of good leadership will be able to increase the achievement motivation of IPS teachers; (2) the leadership of the principal has a direct and indirect effect on teacher performance through the achievement motivation of social studies teachers at Pekanbaru Private Middle School. The meaning of principal leadership can improve teacher performance by increasing the achievement motivation of social studies teachers; and (3) achievement motivation has an effect on the performance of social studies teachers. The meaning of good achievement motivation will be able to improve the performance of social studies teachers at Pekanbaru Private Junior High School.